Pancasila Democracy According to Sukarno's Thought and its Potential for Formulation a New Model of Indonesian Democracy - Razuni, Ganjar (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
Until now, the concept of Pancasila democracy has not been formulated properly and comprehensively. Moreover, this formulation is based on the thoughts of the Pancasila explorers, namely; Ir. Sukarno. The absence of a formulation of the democratic concept of Pancasila based on Sukarno's thinking is caused by the process of dehistoricization of Pancasila that has occurred since the New Order. In fact, both in his Speech on June 1 1945 and at the Pancasila Course Session on People's Sovereignty Principles on July 22 1958, Sukarno explained his various thoughts about the principles of democracy in Pancasila. Sukarno's thoughts on Pancasila democracy have potential for the formulation of a new model of Pancasila Democracy, which is different from other models of democracy, especially the liberal democracy model. Therefore, the formulation of a new Pancasila model of democracy based on Sukarno's thinking is an urgent scientific need and is our common concern.